Implementasi Strategi Pemasaran Digital Untuk Memperluas Jangkauan Pasar Toko Kia Mitra - Hesniati, Hesniati; Carol, Carol (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Toko Kia Mitra is a business engaged in the provision of building equipment that has been operating for more than 20 years in Batam, faces challenges in utilizing digital marketing to expand its market reach. This study aims to implement a digital marketing strategy, including the creation of a logo, Instagram social media account, Google Maps update, and the development of a Linktree, to enhance the store's visibility and sales. Through observation and interviews, the applied solutions successfully increased customer reach, with a rise in Instagram followers and the use of other digital platforms. The implementation results showed an increase in visitors and effectiveness in providing product information while facilitating customer transactions. However, there are still opportunities for further development in content management and customer reviews to achieve more optimal results.